O efeito de um programa de gestão de casos para prevenção de quedas em aspectos da funcionalidade de pessoas idosas: um ensaio clínico randomizado - Lopes, Juliana Ferreira (Universidade Federal de São Carlos, 2023)
Introduction. In view of the increase in population aging and the greater risk of recurrent falls in this population (≥2 falls in the last 12 months), there is a need for fall prevention programs with case management aimed at promoting the functionality of the elderly. The Activity and Participation components are discussed, according to the International Classification of Functioning, Disability and Health (ICF) since it is a useful structure for the multifactorial understanding of falls. Objective. Evaluate the functionality of elderly fallers participating in a fall prevention and case management program. Method. This is a unicentric controlled Randomized Clinical Trial, parallel group (Intervention Group-GI and Control Group-CG) and single-blind (evaluators); composed of Initial Assessment (IA) and Follow-up after 22 weeks. 62 elderly people with recurrent falls, Brazilians and non-institutionalized, participated remotely. Sociodemographic characteristics, health conditions, self-rated health, functionality were investigated through the assessment of disability in activities and restriction in participation by WHODAS, Instrumental Activities of Daily Living (Lawton scale), level of physical activity (modified Baecke Questionnaire for elderly-QBMI), characterization and description of falls (Falls Risk Score) and concern about falling by FES I. There was coding by ICF category for WHODAS and Lawton. Descriptive and inferential statistical analysis, Mann Whitiney and Kruskall Wallis tests (p≤0.05) were performed (SPSS 20.0 program). The dependent variable is related to the functionality described in WHODAS 2.0. The independent variables were: physical activity level, General Health Self-Assessment - AGS, education, age, number of reported falls and IADL. The CG was encouraged to maintain their daily activities. The IG was accompanied by a case management, physical and cognitive training team. The analysis of the study occurred in the manuscripts: 1) Functionality Analysis among the total sample of elderly people; 2) Analysis of variables between program groups. Results. The total AI sample showed a prevalence of females (88.71%), widowers (46.77%), Caucasians (82.26%), Southeast region (87.10%), polypharmacy (50.0%), Regular AGS (43.55%), indication for recurrent falls (69.35%) and partial dependence for IADLs, higher averages for involvement in household activities (me=1.3) and household chores -WHODAS (me =50) (CIF: d630-d649). The WHODAS total score had a negative and strong correlation with the IADL (r=-0.709); negative and moderate with years of education (r=-0.524) and AGS (r=-0.588); positive and moderate with age (r=0.553); positive and strong with the number of falls (r= 0.090). Falls were frequent at home (67.74%) leading mainly to bruises (38.71%) and fear of falling again (66.13%). No significant difference was found between groups for functionality and IADLs. In the Follow up, the GI showed a decrease in means in domains D2 (me=28), D4 (me=0), D5.1 (me=30) and D6 (me=27) when compared to the initial assessment. Conclusion.The Program promoted remote monitoring, identifying functional limitations in the participants.
The effect of a case management program for falls prevention on aspects of the functioning of elderly people: a randomized clinical trial
Keywords: Acidentes por quedas; Prevenção de acidentes; Accident prevention; Accidental falls; Saúde do idoso; Health of the elderly; CIENCIAS DA SAUDE